2013
DOI: 10.1093/infdis/jit637
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Lysin CF-301 and Antibiotic Is Superior to Antibiotic Alone for Treating Methicillin-Resistant Staphylococcus aureus–Induced Murine Bacteremia

Abstract: Lysins are bacteriophage-derived enzymes that degrade bacterial peptidoglycans. Lysin CF-301 is being developed to treat Staphylococcus aureus because of its potent, specific, and rapid bacteriolytic effects. It also demonstrates activity on drug-resistant strains, has a low resistance profile, eradicates biofilms, and acts synergistically with antibiotics. CF-301 was bacteriolytic against 250 S. aureus strains tested including 120 methicillin-resistant S. aureus (MRSA) isolates. In time-kill studies with 62 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
189
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(200 citation statements)
references
References 41 publications
9
189
0
2
Order By: Relevance
“…We previously demonstrated antibiofilm activity for CF-301 against S. aureus strain BAA-42 (43). This analysis was extended here to show that CF-301 (at the MIC of 32 g/ml) can disrupt BAA-42 biofilms on 24-well polystyrene plates within 2 h and prevent regrowth over 24 h (Fig.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…We previously demonstrated antibiofilm activity for CF-301 against S. aureus strain BAA-42 (43). This analysis was extended here to show that CF-301 (at the MIC of 32 g/ml) can disrupt BAA-42 biofilms on 24-well polystyrene plates within 2 h and prevent regrowth over 24 h (Fig.…”
supporting
confidence: 70%
“…Aggressive antibiotic therapies can reduce biofilms and control dispersed planktonic bacteria; however, eradication is difficult because of the high antibiotic concentrations that must be sustained (50,(52)(53)(54). To avoid the limitations of antibiotics, a promising new strategy was proposed based on the emerging understanding of bacteriophage lysins as antibiofilm agents (32,43). Lysins can potentially destroy biofilms, kill constituent bacteria, and resensitize released planktonic bacteria to antibiotics and immune surveillance, and, in doing so, provide effective standalone or adjunctive therapies to treat biofilm infections.…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of endolysins and antibiotics have been reported to be superior to antibiotics alone (42). To evaluate the potential of Art-175 as a supplement to existing antibiotic therapies, Art-175 was combined with ciprofloxacin and tobramycin, and its effect was compared to that of monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Carlson et al 43 suggested that the bacteriostatic effect of HA may be due to the saturation of the bacterial hyaluronate lyase by the excess HA, which prevents the bacteria from maintaining elevated levels of tissue permeability and penetrating the physical defenses of the host. This would enhance the ability of the host's immune system to eradicate MRSA involved β-lysin, which is responsible for blood clotting found after platelets activation [44][45] . β-lysin, which is one of the most abundant compound found in PL after activation 46 has been described to act against bacteria cell-wall, rapidly killing and stopping bacteria reproduction [44][45] , which could explain the results from this study.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…This would enhance the ability of the host's immune system to eradicate MRSA involved β-lysin, which is responsible for blood clotting found after platelets activation [44][45] . β-lysin, which is one of the most abundant compound found in PL after activation 46 has been described to act against bacteria cell-wall, rapidly killing and stopping bacteria reproduction [44][45] , which could explain the results from this study. In addition, other PL-derived molecules with antibacterial properties against Gram+ bacteria could be involved in this response, such as neutrophil activating protein-2 demonstrated capacity to kill Gram-positive and Gram-negative bacteria [47][48] .…”
Section: Antimicrobial Activitymentioning
confidence: 99%